(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
The promotion of oral health in adolescence is a key aspect of general health care. Pubertal girls, aged 13–17, undergo significant hormonal, psychological, and social changes that can influence their susceptibility to dental diseases. While treatment remains an essential component of dental care, the focus on primary prevention is increasingly recognized as a cost-effective and sustainable strategy. Primary prevention aims to reduce the incidence of disease before clinical symptoms appear, through health education, early intervention, and risk factor control. Despite widespread acknowledgment of the importance of dental prevention, there is limited research on how effectively healthcare professionals apply preventive strategies among adolescents, particularly pubertal girls. This study seeks to fill this gap by exploring both the prevalence of dental diseases in this group and the actual involvement of dental practitioners in preventive efforts.